Pemikiran Ibnu Khaldun Tentang Mekanisme Pasar - Wulpiah, Wulpiah (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2016)
Ibnu Khaldun is a thought-leader who is proficient in the various fields of study such as politics, social, philosophy, history, and economy. So, Ibnu Khaldun is known as one of the originators of economic theory and as the largest Muslim economists recognized by Western economists. Unlike previous scholars who had tendencies to be normative, Ibnu Khaldun used historical and social approach to understand economy of a nation. Ibnu Khaldun was very positive in comprehending economy. So, his ways of thinking will be very worthy to put forward in this paper, especially on market mechanisms. Market is a place where buyers and sellers meet and do transactions of buying and selling goods or services. The importance of market in Islam cannot be separated from the function of the market as a place for buying and selling activities. Sale and purchase itself has an important function, since buying and selling are parts of the economic activities which are